2015
DOI: 10.3390/nu7031978
|View full text |Cite
|
Sign up to set email alerts
|

Allomyrina dichotoma (Arthropoda: Insecta) Larvae Confer Resistance to Obesity in Mice Fed a High-Fat Diet

Abstract: To clarify the anti-obesity effect of Allomyrina dichotoma larvae (ADL), we previously reported that ADL block adipocyte differentiation on 3T3-L1 cell lines through downregulation of transcription factors, such as peroxisome proliferator-activated receptor-γ (PPARG) and CCAAT/enhancer binding protein-α (CEBPA). In this study, we tested whether ADL prevent obesity in mice fed a high-fat diet (HFD) and further investigated the mechanism underlying the effects of ADL. All mice were maintained on a normal-fat die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…There has been an interest in developing effective bioactive products using beetles for health supplements or functional foods because of their nutrient components such as unsaturated fatty acids, proteins, vitamins, fiber, and minerals [11,32,33]. Recently, it was reported that Protaetia brevitarsis larvae (PBL) or Allomyrinal dichotoma larvae (ADL) have antioxidant, hepatoprotective, anti-neoplastic, and antiobesity properties [11,20,22,34]. In particular, ADL inhibited the differentiation of adipocytes through the downregulation of adipogenic or lipogenic transcription factors [11,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been an interest in developing effective bioactive products using beetles for health supplements or functional foods because of their nutrient components such as unsaturated fatty acids, proteins, vitamins, fiber, and minerals [11,32,33]. Recently, it was reported that Protaetia brevitarsis larvae (PBL) or Allomyrinal dichotoma larvae (ADL) have antioxidant, hepatoprotective, anti-neoplastic, and antiobesity properties [11,20,22,34]. In particular, ADL inhibited the differentiation of adipocytes through the downregulation of adipogenic or lipogenic transcription factors [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that Protaetia brevitarsis larvae (PBL) or Allomyrinal dichotoma larvae (ADL) have antioxidant, hepatoprotective, anti-neoplastic, and antiobesity properties [11,20,22,34]. In particular, ADL inhibited the differentiation of adipocytes through the downregulation of adipogenic or lipogenic transcription factors [11,22]. In addition, central administration of an ethanol extract of ADL reduced food intake and body weight through the regulation of appetite-related neuropeptides in high-fat diet (HFD)-fed mice [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Korean horn beetle, Allomyrina dichotoma (Linné 1771) is one of the major insects whose larvae have been consumed as traditional oriental medicine for liver disease and diabetes for a long time. Moreover, it has been reported that extracts from A. dichotoma larvae offer various biological benefits such as antibacterial (Niu et al 2016;Koyama et al 2006;Sagisaka et al 2001), anti-Alzheimer's disease (Kim et al 2014), anti-obesity (Kim et al 2016;Yoon et al 2015;Chung et al 2014), and antioxidant effects (Suh et al 2010).…”
Section: Introductionmentioning
confidence: 99%